The Contribution of Local Wisdom in the Green Governance Framework in Bromo Tengger Semeru National Park - Wishnu Mahendra Wiswayana; Primadiana Yunita; Firstyarinda Valentina Indraswari; Ella Joy Avellanoza Ponce (Yayasan Keluarga Guru Mandiri, 2024)
Taman Nasional Bromo Tengger Semeru (TNBTS), home to the Tengger Tribe, is being developed by the government to become a major tourist destination as a part of the